Improving soil fertility through training in the “Garden Island of Fiji” - Madigibuli, Serenia (Technical Centre for Agricultural and Rural Cooperation, 2018)
A non-governmental organisation that has a history of working with rural families spanning over 40 years – Tutu Rural Training Centre (TRTC) – launched a project in 2015 to improve education surrounding soil degradation on the island of Taveuni in Fiji. Through the training of youths in the use of nitrogen-fixing crops and the environmental issues caused by some chemicals, TRTC set about restoring the fertility of the island’s soil in the wake of damage caused by climate change.